2022
DOI: 10.17275/per.22.45.9.2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Technology Assisted Teaching on Success in Mathematics and Geometry: A Meta-Analysis Study

Abstract: In this research, experimental studies comparing the effectiveness of technology-assisted teaching to traditional method up on mathematical and geometry success are combined through meta-analytical review method. For that purpose, articles, master’s, and doctoral theses carried out between the years 2000-2016 in Turkey are examined. 98 studies on academic achievement meet the specified criteria and thus were included in the meta-analysis and the effect size between variables has been demonstrated by assembling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…It was observed that interest in this subject of study has been expressed in educational journals, but it is no less relevant that they were also published in journals specialized in mathematics and science. In fact, more than 80% of the studies in this review address the effects of ICT use on mathematics and science learning, as these are the curricular areas in which researchers are most interested to discover how the educational use of ICT affects students' learning outcomes (Liao and Chen, 2021;Çavuş and Deniz, 2022).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It was observed that interest in this subject of study has been expressed in educational journals, but it is no less relevant that they were also published in journals specialized in mathematics and science. In fact, more than 80% of the studies in this review address the effects of ICT use on mathematics and science learning, as these are the curricular areas in which researchers are most interested to discover how the educational use of ICT affects students' learning outcomes (Liao and Chen, 2021;Çavuş and Deniz, 2022).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A lot of previous secondary studies combining between systematic review and meta-analysis related to ICT-based or -assisted mathematics learning and mathematics academic achievement have been conducted massively. Some metaanalysis studies found that computer technology -assisted mathematics education had significant positive effect in enhancing students' mathematics achievement [9,10,13,[84][85][86][87][88]. Particularly, other few meta-analysis studies revealed that the utilization of mathematics software also had significant positive effect on students' mathematics learning outcomes [82,[89][90][91].…”
Section: Relevant Secondary Studiesmentioning
confidence: 99%
“…Numerous meta-analysis studies regarding ICT-based orassisted mathematics learning and mathematics achievement examined the involvement of several substantial factors, such as educational level [9,10,84,85], instrument [13,[86][87][88], participant [82,89,91,103], intervention duration [92][93][94]104], class capacity [11,96,97], mathematical content [98][99][100]105], and school geographical location [10,106]. Moreover, some meta-analysis studies found that those factors, such as class capacity, educational level, intervention duration, participant, mathematical content, instrument, and school geographical location significantly differentiated students' mathematics achievement in ICT-based or -assisted mathematics learning [9-11, 86, 88, 91, 93, 94, 97, 100, 101].…”
Section: Substantial Factormentioning
confidence: 99%
See 1 more Smart Citation
“…[47], [24], [25], [26], [48], [49], [27], [28], [50], [51], [26], [52], [53], [54], [55], [29], [30], [56], [3], [57] Multimedia These articles denote that the uses of multimedia applications achieve a better environment for cognitive development and improve academic performance. Where every visual demonstration is important for training.…”
Section: Categories Themes and Functionality Referencesmentioning
confidence: 99%